A Model of Natural Enemies of the Main Pest Hypothenemus Hampei in People's Coffee Plantations in the Lake Toba Area - Retna Astuti Kuswardani (Journal of Global Innovations in Agricultural Sciences)
The increase in coffee plantation area in the Lake Toba area is dominated by 96% of smallholder plantations. The coffee productivity value is relatively low, which is 810 kg/ha/year compared to the productivity that should reach 2000 kg/ha/year. Farmers have had a long experience, but are not supported by cultivation techniques according to Good Agricultural Practices (GAP) coffee will trigger an increase in attacks by Plant Pest Organisms. Attacks by the coffee berry borer (CBB) Hypothenemus hampei and leaf-sucking pests Helopelthis sp. can reduce production by up to 50%. The results of the first year's research showed that attacks by leaf-sucking pests Helopelthis sp. spread with an attack intensity ranging from 40.38% to 59.61%, causing the shoots to dry out and rosettes to occur. In addition, the relative density of CBB in monoculture coffee planting patterns can reach 27 individuals/night/trap so that farmers' dependence on pesticides continues to increase. The occurrence of this pest problem is one indicator of the imbalance of the coffee plantation ecosystem. The utilization of coffee plantation areas in monoculture has not provided added value per planting area, even though various types of annual plants, both food crops and horticultural plants in the area have the potential to be utilized. Although natural enemies of CBB and Helopelthis sp. have been found, there is no information on optimizing the use of natural enemies either by manipulating habitats or applying entomopathogens in the field. The aim of the research was to obtain the type of planting pattern that supports the existence of natural enemies and to obtain biological agents endemic to coffee plantations in the Lake Toba area that have the potential to control CBB. The method used was to increase vegetation diversity, optimize protective plants and augment natural enemies of CBB and Helopelthis sp. as the basis for managing Sustainable Coffee Plantation Pests in the Lake Toba Area. The results of the study showed that increasing the diversity of coffee plantation vegetation (polyculture) could reduce abundance almost twofold and suppress the level of CBB attacks by up to 30.76% compared to monoculture planting patterns. Biological agents of entomopathogenic fungi Beauveria sp. and Metarhizium sp. The results of exploration in coffee plantations were also able to kill CBB using the spraying and fruit soaking methods, namely 47.50% and 100% respectively. The conclusion of the study is that polyculture planting patterns can suppress the CBB population. In addition, two types of entomopathogenic fungi were obtained that have the potential to control CBB, including Beauveria sp. and Metharizium sp. Keywords: Augmentation, coffee berry borer (CBB) Hypothenemus hampei, conservation, polyculture, vegetation.